Evaluasi Usability dan Perbaikan Antarmuka Pengguna Aplikasi Malang e-Policing dengan Pendekatan Human Centered Design - Imam Safi'i; Komang Candra Brata; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Polres Malang launched the application of Malang e-Policing which is used for the activities of serving the community both in terms of recording, addressing criminal reporting, counseling/socialization of criminal acts, dissemination of information and other needs. However, the app still has complaints from users related to usability, such as too small and stacked background, no back button in some menus, and no edit button in profile settings. This research aims to evaluate the usability and improvement of the application interface of Malang e-Policing with Human Centered Design (HCD). HCD is an approach to system design and development that is more interactive with a focus not only to the user but also stakeholders. On the first stage HCD is understand and specify the context of use which generates identification of users, stakeholders, user characteristics, tasks and objectives, as well as the system environment. The second phase of Specify the user requirements, done with usability testing, the QUIS questionnaire, and interviews resulted in 14 usability and interface issues. Third is produce design solutions from this stage resulting in a draft information architecture, wireframe, mockup, and prototype. The fourth or final stage is Evaluate the design with the results of the value learnability 99.75%, efficiency 99.7%, errors 0.07%, memorability facet of 15.15% and the number of taps 9.36%, as well as satisfaction 95.46%. From the evaluation results can be concluded the repair design gives a good impact on the application usability Malang e-Policing.